Prognostic Models of Mortality from Accidental Severe Traumatic Brain Injury in Children and Adolescents: A Systematic Review - Jose Roberto Tude Melo; Marcelo Liberato Coelho Mendes de Carvalho (Brazilian Society for Pediatric Neurosurgery, 2021)
Introduction: Prognostic models are statistical models that combine two or more items of patient data to predict clinical outcomes. Objective: Identify prognostic models of mortality developed and published in the medical literature for possible applicability in children and adolescents victims of severe traumatic brain injury (TBI). Methods: Systematic review in the Medline electronic database (PubMed platform) of scientific articles published from 2006 (year of publication of the last systematic review on prognostic models for TBI before 2017) until July 29, 2017. Results: Ten studies on prognostic models of mortality in children and adolescents victims of severe TBI were identified for final inclusion in the review. There were eight development and two validation studies conducted in different countries. Conclusion: The analysis of this systematic review makes it possible to conclude that the ten prognostic models included in the final sample provide health professionals with a scientific evidence-based understanding of the severity of pediatric victims of severe TBI. This systematic review is classified as presenting 2A and 1 level of evidence (systematic review of homogeneous cohorts), according to the 2009 and 2011 classifications, respectively, of the Oxford Center for Evidence-Based Medicine